Autoimmune pulmonary alveolar proteinosis presenting peripheral ground‐glass opacities. Issue 1 (13th November 2018) - Sugino, Keishi; Ando, Masahiro; Mori, Kiyoshi; Tsuboi, Eiyasu
Abstract : Autoimmune pulmonary alveolar proteinosis should be considered in the differential diagnosis of peripheral ground‐glass opacities. Abstract : Autoimmune pulmonary alveolar proteinosis should be considered in the differential diagnosis of peripheral ground glass opacities.